2017
DOI: 10.12793/tcp.2017.25.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pharmacokinetic characteristics of sildenafil citrate chewable tablets and film-coated tablets in healthy male subjects

Abstract: UI14SDF100CW is a chewable tablet of sildenafil citrate, which was developed to improve compliance through convenience of administration. The purpose of this study was to compare the pharmacokinetic (PK) properties of sildenafil citrate chewable tablets (UI14SDF100CW) and conventional sildenafil citrate film-coated tablets (Viagra®, Pfizer). A randomized, open-label, single dose, two-treatment, two-period, two-way crossover study was conducted in 60 healthy male volunteers. In each period, the subjects receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Statistically important reduction in absorption rate is observed whereas sildenafil is co-administered with high fat meal (delayed t max by 1 h in fed state compared to 30–120 min t max in fasted state, 90% confidence intervals CI: 0.7 ± 1.5 using ANOVA appropriate design) as well as in mean C max (−29% in fed state, 90% CI: 19 ± 38) [ 60 ]. The combination of food effects with the diminished bioavailability due to extensive first path metabolism [ 60 ], has led contemporary researchers to focus on upgrading the existing oral dosage formulations [ 96 , 97 , 98 , 99 , 100 ] and even apply alternative routes of administration i.e., intranasal, transdermal and intravenously [ 101 , 102 , 103 ].…”
Section: Alternative Administration Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistically important reduction in absorption rate is observed whereas sildenafil is co-administered with high fat meal (delayed t max by 1 h in fed state compared to 30–120 min t max in fasted state, 90% confidence intervals CI: 0.7 ± 1.5 using ANOVA appropriate design) as well as in mean C max (−29% in fed state, 90% CI: 19 ± 38) [ 60 ]. The combination of food effects with the diminished bioavailability due to extensive first path metabolism [ 60 ], has led contemporary researchers to focus on upgrading the existing oral dosage formulations [ 96 , 97 , 98 , 99 , 100 ] and even apply alternative routes of administration i.e., intranasal, transdermal and intravenously [ 101 , 102 , 103 ].…”
Section: Alternative Administration Schemesmentioning
confidence: 99%
“…In order to avoid the disadvantages of the film-coated tablet i.e., poor patient compliance owing to swallowing difficulties Yoo et al prepared chewable sildenafil tablets. In detail, C max and AUC last geometric mean ratios for 90% CI, indicated bioequivalence between the chewable sildenafil tablet 0.933 (0.853–1.021) and the marketed one 1.034 (0.964–1.108), within the Korean bioequivalence criterion of 0.80 to 1.25 [ 99 ]. The clinical study was conducted in 60 healthy male volunteers and concluded that the chewable tablet showed similar pharmacokinetic properties to the market product and therefore can be an alternative to sildenafil for the treatment of erectile dysfunction, providing better compliance [ 99 ].…”
Section: Alternative Administration Schemesmentioning
confidence: 99%